Effectiveness of cognitive behavioral therapy-based intervention in preventing gaming disorder and unspecified internet use disorder in adolescents: a cluster randomized clinical trial - Lindenberg, Katajun; Kindt, Sophie; Szász-Janocha, Carolin (JAMA network open, 2022)
IMPORTANCE Behavioral addictions were introduced as novel mental disorders in the International Classification of Diseases, 11th Revision, based on evidence that human behavior itself can become addictive, similar to addiction to substances. However, previous studies on prevention of gaming disorder and unspecified internet use disorder lacked randomization, follow-up measurements, and diagnostic interviews that assessed incidence rates; this trial was intended to fill this gap. OBJECTIVES To investigate whether the PROTECT (Professioneller Umgang mit technischen Medien [Professional Use of Technical Media]) intervention can reduce the symptom severity and prevent full syndrome and subthreshold onset of gaming disorder and unspecified internet use disorder in at-risk adolescents. DESIGN, SETTING, AND PARTICIPANTS A multicenter cluster randomized clinical trial conducted recruitment, screening, intervention delivery, and data collection among at-risk adolescents aged 12 to 18 years in 33 high schools in Germany. Inclusion criteria for the study and symptom severity analyses were elevated symptoms of gaming disorder and unspecified internet use disorder. A subsample that met the inclusion criteria for incidence analyses (no full syndrome of gaming disorder or unspecified internet use disorder, depression, or anxiety at baseline) was analyzed for illness onset. Participants were randomized to either the PROTECT intervention group or the assessment-only control group. Participants were assessed at baseline, 1-month follow-up, 4-month follow-up, and 12-month follow-up between October 1, 2015, and September 30, 2018. Based on intent-to-treat principle, data analyses were conducted from February 8, 2019, to May 7, 2021. INTERVENTIONS PROTECT, a theory-driven, manualized, cognitive behavioral therapy-based indicated preventive group intervention that is delivered in 4 sessions by trained psychologists. It targets changes in addictive reward processing and pathological cognitive mechanisms. MAIN OUTCOMES AND MEASURES The primary outcome was symptom severity (measured by CSAS [Computerspielabhangigkeitsskala], a modified German video game dependency scale with a score range of 0-56 [higher scores indicating greater pathology]) along with incidence rates (assessed by a structured clinical interview) after 12 months. Secondary outcomes were comorbid psychopathology and problem behaviors. RESULTS A total of 422 at-risk adolescents (mean [SD] age, 15.11 [2.01] years; 229 female participants [54.3%]) were randomized to either the PROTECT intervention group (n = 167; mean [SD] risk score, 29.05 [6.98]) or the assessment-only control group (n = 255; mean [SD] risk score, 26.21 [5.01]) and were included in the symptom severity analyses. Compared with the control group, the PROTECT group showed a significantly greater reduction in symptom severity of gaming disorder or unspecified internet use disorder (gamma(11) = -0.128; 95% CI, -0.246 to -0.011; P = .03), reflecting a 39.8% vs 27.7% reduction of symptoms with an effect size of Cohen d = 0.67 (baseline vs 12-month follow-up) for the PROTECT group. Differences in incidence rates did not reach statistical significance. The PROTECT group showed a significantly greater decrease in procrastination (gamma(11) = -0.458; 95% CI, -0.735 to -0.180; P < .001) over 12 months, but no significant differences were found for other secondary outcomes. CONCLUSIONS AND RELEVANCE Results of this trial showed that the PROTECT intervention effectively reduced symptoms of gaming disorder and unspecified internet use disorder over 12 months. The intervention did not change incidence rates of gaming disorder or unspecified internet use disorder.